Arterial Wall Compliance of the Lower Limb Arteries in Healthy Adults—A Systematic Review and Meta-Analysis - Cathryn Bassett; Bernhard Hruschka; Saurav Ranjan Mohapatra; Jelle Frankort; Pauline Riedl; Eva Kalkum; Christian Uhl; Alexander Gombert; Panagiotis Doukas (Journal of Clinical Medicine, 2026)
Background/Objectives: Arterial wall compliance is a key biomechanical property influencing local hemodynamics, vascular remodeling, and surgical performance. Despite its clinical relevance, reference values in lower limb arteries remain insufficiently characterized. This systematic review and meta-analysis aimed to synthesize existing evidence on cross-sectional compliance (CC) of the common femoral artery (CFA), superficial femoral artery (SFA), and popliteal artery (PA) in healthy adults. Methods: A systematic literature search was performed according to PRISMA guidelines to identify studies reporting arterial wall compliance in healthy adults. Study characteristics, measurement techniques, and compliance values were extracted. Risk of bias was assessed using a QUADAS-2/COSMIN-based tool. Pooled estimates were calculated using random effects meta-analysis, PROSPERO CRD420251208399. Results: Thirty-four studies with a total of 3452 participants were included. Reported compliance values varied substantially. The pooled mean CC of the CFA was 0.95 (95%-CI 0.83–1.06, I2 = 99.2%). Sex-specific analysis showed a pooled mean CC of 1.07 (95%-CI 0.87–1.28, I2 = 99.0%) in males and 0.90 (95%-CI 0.75–1.05, I2 = 83.6%) in females. Meta-regression of age, sex, and BMI did not significantly demonstrate association between these moderators and CC or explain observed heterogeneity. Extracted CC values of the SFA ranged from 0.17 to 0.50 mm2/kPa, and mean CC values of the PA ranged from 0.44 to 0.62 mm2/kPa. Conclusions: Available data on CC in lower limb arteries are limited and heterogeneous. Given the substantial between-study heterogeneity, the pooled estimates resulting from the meta-analysis should therefore be considered descriptive and should not be interpreted as definitive physiological reference values.